2013
DOI: 10.1021/am301920r
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Gelation of Silica Nanoparticles and a Sorbitol-Based Molecular Gelator to Yield Highly-Conductive Free-Standing Gel Electrolytes

Abstract: Lithium-ion batteries have emerged as the preferred type of rechargeable batteries, but there is a need to improve the performance of the electrolytes therein. Specifically, the challenge is to obtain electrolytes with the mechanical rigidity of solids but with liquid-like conductivities. In this study, we report a class of nanostructured gels that are able to offer this unique combination of properties. The gels are prepared by utilizing the synergistic interactions between a molecular gelator, 1,3:2,4-di-O-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…107 It is worth noting that FS did not itself form a gel in the mentioned solvent, but helped rigidify the resulting organogel via non-covalent cross-linking between the silanol (Si-OH) groups of FS and the free hydroxyl groups of MDBS. 107 It is worth noting that FS did not itself form a gel in the mentioned solvent, but helped rigidify the resulting organogel via non-covalent cross-linking between the silanol (Si-OH) groups of FS and the free hydroxyl groups of MDBS.…”
Section: Gel Electrolytes For Future Energy Technologiesmentioning
confidence: 99%
“…107 It is worth noting that FS did not itself form a gel in the mentioned solvent, but helped rigidify the resulting organogel via non-covalent cross-linking between the silanol (Si-OH) groups of FS and the free hydroxyl groups of MDBS. 107 It is worth noting that FS did not itself form a gel in the mentioned solvent, but helped rigidify the resulting organogel via non-covalent cross-linking between the silanol (Si-OH) groups of FS and the free hydroxyl groups of MDBS.…”
Section: Gel Electrolytes For Future Energy Technologiesmentioning
confidence: 99%
“…The self-assembly of small functional molecules into supramolecular structures is a powerful approach toward the development of new nanoscale materials and devices [1-7]. As a novel class of self-assembled materials, low weight molecular organic gelator (LMOG) gels organized in regular nanoarchitectures through specific noncovalent interactions including hydrogen bonds, hydrophobic interaction, π-π interactions, and van der Waals forces have recently received considerable attention [8-13].…”
Section: Introductionmentioning
confidence: 99%
“…3. Obviously, the ionic conductivities of all the polymer electrolytes rise quickly with increasing temperature, 43,44 and the plots of the ionic conductivity are non-linear, it was confirmed that their conductivities follow the Vogel-Tamman-Fulcher (VTF) equation. [45][46][47] This non-linear VTF behavior is mainly attributed to the complexing segments of the amorphous PEG chain with Li ions, which assisted ions transport through the polymer electrolyte membrane rather than the pores of polymer electrolyte membrane, also, this phenomenon can also be seen in Fig.2 (d)-(e).…”
Section: The Ionic Conductivity Of Paek-40% Peg With Liclo 4 Solid Pomentioning
confidence: 89%